Motion-partitioned adaptive block matching for video compression - Huang, Yan; Zhuang, Xinhua (1995)
We present a motion compensation technique called motion-partitioned adaptive block matching algorithm (MPA-BMA) for motion compensated video compression. The algorithm offers a good degree of scene adaptation to reduce prediction errors while maintaining a slightly increased amount of side motion data and being computationally affordable. It detects the motion boundaries, partitions the motion field into consistent motion groups and computes more reliable motion data by using variable-sized matching blocks that are adaptively composed. Experiments compare its good performance with the full-search block matching algorithm (BMA)
Formato de archivo: PDF. -- Disponible también en línea vía suscripción BECyT (Cons. 23/04/2009)
Proceedings of International Conference on Image Processing (ICIPྛ) Vol. 1, pp. 554-557.
Keywords: PROCESAMIENTO DE IMÁGENES; VIDEO; COMPRESIÓN DE DATOS; MOVIMIENTO